Examining the effects of students' self-efficacy and prior knowledge on learning and visual behavior in a physics game. (March 2022) - Wang, Jiahui; Stebbins, Abigail; Ferdig, Richard E.
Abstract: Research has provided evidence of the significant promise of using educational games for learning. However, there is limited understanding of how individual differences (e.g., self-efficacy and prior knowledge) affect visual processing of game elements and learning from an educational game. This study aimed to address these gaps by: a) examining the effects of students' self-efficacy and prior knowledge on learning from a physics game; and b) exploring how learners with distinct levels of self-efficacy and prior knowledge differ in their visual behavior with respect to the game elements. The visual behavior of 69 undergraduate students was recorded as they played an educational game focusing on Newtonian mechanics. Individual differences in self-efficacy in learning physics and prior knowledge were assessed prior to the game, while a comprehension test was administered immediately after gameplay. Wilcoxon signed-rank tests showed that all participants significantly improved in their understanding of Newtonian mechanics. Mann-Whitney U tests indicated learning gains were not significantly different between the groups with varying levels of prior knowledge or self-efficacy. Additionally, a series of Mann-Whitney U tests of the eye tracking data suggested the learners with high self-efficacy tended to pay more attention to the motion map - a critical navigation component of the game. Further, the high prior knowledge individuals excelled in attentional control abilities and exhibited effective visual processing strategies. The study concludes with important implications for the future design of educational games and developing individualized instructional support in game-based learning. Highlights: Educational games are used by learners with varying characteristics in proficiencies and interests. It is not clear how learners with different levels of prior knowledge and self-efficacy process game elements. The study used eye tracking technology to study learners' visual attention to various elements within a physics game. High self-efficacy learners attended more to a critical area that helped guide navigation through the game challenges. High prior knowledge learners excelled in attentional control and exhibited effective visual processing strategies.